INTERTEKSTUALITAS PUISI “PADAMU JUA” AMIR HAMZAH DAN PUISI “DOA” CHAIRIL ANWAR: Menelusuri ‘Cahaya’ al-Qur’an dalam Puisi Sufistik Indonesia - Ali Imron Al-Mar'ruf (Universitas Muhammadiyah Surakarta, 2005)
The study focussed on the intertextual analysis of poems “Padamu Jua”, masterpieceof Amir Hamzah and “Doa”, masterpiece of Chairil Anwar. The study aims todescribe: (1) the intertexts relation of the poem “Padamu Jua” and “Doa”; (2) the influenceof the poem “Padamu Jua” as hypogram on the poem “Doa”; and (3) to describethe possibility of the al-Qur’an as an inspiration source. The research method is qualitativesince it uses participant observation technique. This means that the researcher getsinto the realms of data, comprehends them, and continuously systematizes the object ofstudy. The object of study is the intertextualities of the two poems while the data arequalitative types in the form of verbal word or discourse within the poem text. The resultof study shows that: (1) there is intertextual relation between the poem “Padamu Jua”and “Doa”; the poem “Padamu Jua” is as a hypogram while the poem “Doa” is as itstransformation; (2) directly or indirectly, the poem “Padamu Jua” and the poem “Doa”can be seen on the structure, the imagination use, and a slight different expression of itstheme; (3) there is a strong tendency that the two poems constitute the Indonesian sufisticbellesletters inspired by the al-Qur’an verse “Light of above Light” ( S. an-Nur: 35) asits hypogram. Therefore, the two poems are categorized as highly valuable works whichare successfully to integrate the devine and human dimension.